Development and characterization of influenza M2 ectodomain and/or hemagglutinin stalk-based dendritic cell-targeting vaccines - Olukitibi, Titus Abiola; Ao, Zhujun; Azizi, Hiva; Mahmoudi, Mona; Coombs, Kevin; Kobasa, Darwyn; Kobinger, Gary; Yao, Xiaojian (Frontiers in Microbiology, 2022)
A universal influenza vaccine is required for broad protection against influenza infection. Here, we revealed the efficacy of novel influenza vaccine candidates based on Ebola glycoprotein (EboGP) DC-targeting domain (EΔM) fusion protein technology. The four copies of extracellular matrix protein of influenza (tM2e) or M2e -hemagglutinin stalk (HA stalk) peptides (HM2e) were fused with EΔM to generate EΔM-tM2e or EΔM-HM2e, respectively. We demonstrated that EΔM-HM2e- or EΔM-tM2e-pseudotyped viral particles (PVPs) can efficiently target DC/macrophages in vitro and induced significantly higher titers of anti-HA and/or anti-M2e antibodies in mouse. Significantly, the recombinant vesicular stomatitis virus (rVSV)-EΔM-tM2e and rVSV-EΔM-HM2e vaccines mediated rapid and potent induction of M2 or/and HA antibodies in mouse serum and mucosa. Importantly, vaccination of rVSV-EΔM-tM2e or rVSV-EΔM-HM2e protected mice from influenza H1N1 and H3N2 challenges. Taken together, our study suggests that rVSV-EΔM-tM2e and rVSV-EΔM-HM2e are promising candidates that may lead to the development of a universal vaccine against different influenza strains.